Tumor antigens discovery: perspectives for cancer therapy. - Wang, R. F. (The Feinstein Institute for Medical Research, 1997)
The adoptive transfer of cytotoxic T lymphocytes (CTLs) derived from tumor-infiltrating lymphocytes (TIL) along with interleukin 2 (IL-2) into autologous patients with cancer resulted in the objective regression of tumor, indicating that these CTLs recognized cancer rejection antigens on tumor cells. To understand the molecular basis of T cell-mediated antitumor immunity, several groups started to search for such tumor antigens in melanoma as well as in other types of cancers. This led to the subject I will review in this article. A number of tumor antigens were isolated by the use of cDNA expression systems and biochemical approaches. These tumor antigens could be classified into several categories: tissue-specific differentiation antigens, tumor-specific shared antigens, and tumor-specific unique antigens. However, the majority of tumor antigens identified to date are nonmutated, self proteins. This raises important questions regarding the mechanism of antitumor activity and autoimmune disease. The identification of human tumor rejection antigens provides new opportunities for the development of therapeutic strategies against cancer. This review will summarize the current status and progress toward identifying human tumor antigens and their potential applications to cancer treatment.